Intra-cyclic analysis of the front crawl swimming technique with an inertial measurement unit - Engel, A.; Schaffert, N.; Ploigt, R.; Mattes, K. (Journal of Human Sport & Exercise, 2022)
Sports scientists and coaches strive to identify and analyse performance relevant parameters and to optimize them in the training practice. In swimming, this process is time-consuming and requires expensive and professional video equipment, which is currently considered the gold standard. Since inertial measurement units (IMUs) are increasingly interesting for athletes, are more easily accessible and are less disturbing to wear, they offer an ideal alternative to classic video-supported motion analysis. In addition, IMUs provide further data of interest to scientists and trainers. The present study aims to transfer the findings from the video analysis data to the data measured with an IMU. The focus is on the frontal crawl and its key movements, body roll, angular velocity and forward acceleration in relation to their intra-cyclic variations. Ten athletes from regional to national level swam 100 m front crawl and the video recording was combined with the IMU to analyse the key positions and find similarities and differences between the swimmers. The findings are the basis for an automatic pattern recognition system to provide coaches and scientists with immediate feedback on the execution of movements and to decide which parameters should be specifically trained to improve performance.